Initiation of fatigue cracks in AZ91 Mg alloy processed by ECAP - Fintová, Stanislava; Kunz, Ludvík (IOP Publishing, 2014)
Mechanism of fatigue crack initiation was investigated in ultrafine-grained (UFG) magnesium alloy AZ91 processed by equal channel angular pressing (ECAP). Fatigue behaviour of UFG material was compared to the behaviour of material in an initial as-cast state. Focused ion beam technique (FIB) was applied to reveal the surface relief and early fatigue cracks. Two substantially different mechanisms of crack initiation were observed in UFG structure, which can be characterized as bimodal even after 6 ECAP passes by route Bc. The bimodality consists in a coexistence of very fine grained areas with higher content of Mg17Al12 particles and areas exhibiting somewhat larger grains and lower density of particles. The fatigue cracks which initiate in areas of larger grains are related to the cyclic slip bands; this initiation mechanism is similar to that observed in cast alloy. The second initiation mechanism is related to the grain boundary cracking which takes place predominantly in the fine grained areas.

Mechanism of fatigue crack initiation was investigated in ultrafine-grained (UFG) magnesium alloy AZ91 processed by equal channel angular pressing (ECAP). Fatigue behaviour of UFG material was compared to the behaviour of material in an initial as-cast state. Focused ion beam technique (FIB) was applied to reveal the surface relief and early fatigue cracks. Two substantially different mechanisms of crack initiation were observed in UFG structure, which can be characterized as bimodal even after 6 ECAP passes by route Bc. The bimodality consists in a coexistence of very fine grained areas with higher content of Mg17Al12 particles and areas exhibiting somewhat larger grains and lower density of particles. The fatigue cracks which initiate in areas of larger grains are related to the cyclic slip bands; this initiation mechanism is similar to that observed in cast alloy. The second initiation mechanism is related to the grain boundary cracking which takes place predominantly in the fine grained areas.
Initiation of fatigue cracks in AZ91 Mg alloy processed by ECAP
Keywords: fatigue crack initiation; fatigue; AZ91 magnesium alloy; fatigue crack initiation; fatigue; AZ91 magnesium alloy